Effects of CLOCK gene variants and early stress on hopelessness and suicide in bipolar depression. (14th September 2015) - Benedetti, Francesco; Riccaboni, Roberta; Dallaspezia, Sara; Locatelli, Clara; Smeraldi, Enrico; Colombo, Cristina
Abstract : Background : Patients with mood disorders show a high dependence of behavior on the molecular characteristics of the biological clock. CLOCK rs1801260 gene polymorphism influences circadian behavior in bipolar disorder (BD), with *C carriers showing a delayed sleep onset and worse insomnia. Sleep phase delay and insomnia associate with suicide in the general population. Methods : We investigated the effects of rs1801260, and of exposure to stressful life events, on current suicidal ideation and history of suicide attempts in 87 depressed patients with BD. Results : rs1801260*C carriers currently showed worse Hamilton Depression Rating Scale scores for suicide and worse ratings for depressive cognitive distortions. Previous history of attempted suicide associated with exposure to higher stressful events in the early life, with rs1801260*C carriers showing a higher dependency of the modeled probability of attempting suicide on the severity of exposure to early stress. Discussion : CLOCK rs1801260 modulated the relationship between early stress, adult history of attempted suicide and current suicide ideation. Factors affecting the biological clock can influence "non-clock" core psychopathological features of mood disorders.